Kesulitan Belajar Membaca (Disleksia) dan Kesulitan Belajar Menulis (Disgrafia) di SDN Cibadak 1 Kecamatan Cikupa - Humaira, Shopie Firda; Muplihah, Zahrotul; Sari, Dita Mayang; Qorina, Siti Asyiva; Anggraini, Puspa; Herros, Putri Raudhah; Azzahra, Nurania (ALSYS, 2022)
Dyslexia is a form of disturbance in the reading process. The form of difficulty in understanding words or sentences. Dysgraphia is a form of disturbance in the writing process. The form of difficulty in involving symbols, sounds, letters or numbers. Dysgraphia is used to describe very poor handwriting. This research uses qualitative research. The research method used by the researcher is descriptive qualitative. Qualitative descriptive, namely explaining the problems in the field. This research was conducted at SDN Cibadak 1 which is located on Jl. Raya Serang No.10, Cibadak, Kec. Cikupa, Tangerang Regency. In this study, the primary data used were Observation, Interview, and Documentation. Based on the results of observations, students at SD Negeri Cibadak 1 have the same types of disabilities, namely reading delays (Dyslexia), and Writing delays (Dysgraphia). Children with dyslexia and dysgraphia are low grade students, there are 3 grade 1 students who have learning delays, 1 grade 2 students who experience writing delays, and 1 grade 3 students who experience learning delays. Learning adjustments made at SD NEGERI CIBADAK 1 continue to use the same curriculum for children with special needs and other students, namely using the 2013 curriculum.